Efeito da estimulação transcraniana por corrente contínua de alta definição (HD-tDCS) e o consumo de Chlorella pyrenoidosa (H. Chick) para tratamento adjuvante da insuficiência cardíaca com fração de ejeção reduzida - Cintra, Vanessa Meira (2024)
Heart failure with reduced ejection fraction (HFrEF) is a complex and multifactorial condition that leads to functional impairments related to disruption in the inflammatory cascade and nutrient depletion, which can impact quality of life and increase hospitalizations. Cardiac surgery is a repair mechanism in HFrEF that has an impact on mortality, elevates inflammatory markers, and requires monitoring. B12 supplementation through Chlorella pyrenoidosa (microalgae - functional food) reduces cardiac damage and modulates the inflammatory cascade. In addition, High-Definition Transcranial Direct Current Stimulation (HD-tDCS), a non-invasive technique capable of modulating neuronal excitability and inducing anti-inflammatory effects. In this sense, the objective was to evaluate the effects of HD-tDCS and the consumption of Chlorella pyrenidosa to improve B12 levels and inflammatory response in patients with HFrEF in the perisurgical period. These are two randomized controlled double-blind clinical trials (RCTs) to evaluate the peri-surgical period. One involved 36 patients hospitalized for surgical procedures using HD-tDCS as a priming for surgery. The other was conducted in an outpatient setting with 26 post-surgical patients with HFrEF who were followed for 30 days. In both studies, baseline and post-treatment assessments were performed. The HD-tDCS protocol consisted of 5 sessions, applied once a day, for a period of up to 5 days before surgery, with stimulation of the Dorsolateral Prefrontal Cortex, with an intensity of 4 mA and a duration of 20 minutes each. At hospital discharge, the groups were reversed, composing the other RCT, and the active group became the intervention group using Chlorella pyreinodosa, whose participants were instructed to consume 10 tablets, 5 g/day, containing 4 mcg of B12, for a period of thirty days. After this period, they returned for nutritional assessment and final exams. Both RCTs obtained a similar participant profile, composed of elderly people, with a high proportion of comorbidities such as arterial hypertension and coronary artery disease, in addition to high levels of overweight, obesity and malnutrition. In the RCT with HD-tDCS as a priming for surgery, a reduction in IL-6 was observed after the protocol [Z=-2.556; p<0.01] reducing the mean [8.35 pg/mL (IIQ4.15) / 4.70 pg/mL (IIQ3.95);]. In the RCT with Chlorella pyreinodosa consumption, a reduction in CRP [adequate CRP T0 = 0% / 50% (CI 25.38-74.62), IL-6 [T0 Increased Risk = 100.0% (CI 75.75-100.0)/ G1 T1 = 66.67% (CI 39.06 - 88.19)]; and NT-Pro-BNP [T0 Increased Risk = 91.67% (CI 61.61-99.57)/ T1 = 25.0% (CI 8.89 - 52.23)] was observed, but without an increase in vitamin B12. Thus, it is considered that the intervention by HD-tDCS was a neuromodulatory and cardiac protection tool in pre-surgical patients with HFrEF in relation to inflammatory marker and the intervention by C. pyreinodosa in patients post-surgical markers of inflammation and cardiac injury, also being a tool for neuro and cardioprotection. The research infers satisfactory findings for reducing inflammatory disruption of HFrEF in the peri-surgical period.